The Linguistics of Newswriting - Perrin, Daniel (John Benjamins Publishing Company, 2013)
The Linguistics of Newswriting focuses on text production in journalistic media as both a socially relevant field of language use and as a strategic field of applied linguistics. The book discusses and paves the way for scientific projects in the emerging field of linguistics of newswriting. From empirical micro and theoretical macro perspectives, strategies and practices of research development and knowledge transformation are discussed. Thus, the book is addressed to researchers, teachers and coaches interested in the linguistics of professional writing in general and newswriting in particular. Together with the training materials provided on the internet www.news-writing.net, the book will also be useful to anyone who wants to become a more "discerning consumer" (Perry, 2005) or a more reflective producer of language in the media.